The Convention on Biological Diversity's 2010 target - Balmford, Andrew; Bennun, Leon; Brink, Ben ten (Himalayan Journal of Sciences, 2007)
Governments are often accused of responding only to short-term and parochial considerations. It is therefore remarkablethat representatives of 190 countries recently committed themselves at the Convention on Biological Diversity toreducing biodiversity loss. This presents conservation biologists with perhaps their greatest challenge of the decade.The authors of this Policy Forum describe approaches to identifying more of the earth’s biological diversity;understanding how biological, geophysical, and geochemical processes interact; and presenting scientific knowledgein time to contribute to and achieve the 2010 target.Himalayan Journal of Sciences 3(5) 2005 p.43-45